Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1103/physrevd.85.123535
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on superconducting cosmic strings from early reionization

Abstract: Electromagnetic radiation from superconducting cosmic string loops can reionize neutral hydrogen in the Universe at very early epochs, and affect the cosmic microwave background temperature and polarization correlation functions at large angular scales. We constrain the string tension and current using WMAP7 data, and compare with earlier constraints that employed cosmic microwave background spectral distortions. Over a wide range of string tensions, the current on the string has to be less than $10 7 GeV.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 73 publications
(93 reference statements)
0
16
0
Order By: Relevance
“…In this work, we have considered non-superconducting strings. Superconducting strings lead to a larger effect, as studied in [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we have considered non-superconducting strings. Superconducting strings lead to a larger effect, as studied in [23].…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the correction to the ionization fraction of hydrogen due to cosmic strings, will follow the approach taken in [23]. Assuming that one photon in the frequency interval between ω i and ω f emitted from the string loop ionizes one hydrogen atom, we can derive the following expression for the ionization fraction due to cosmic strings:…”
Section: Ionization Fraction Of Stringsmentioning
confidence: 99%
“…decaying or annihilating particles [39][40][41][42][43], reionization and structure formation [44][45][46][47][48][49][50][51], primordial black holes [52][53][54], cosmic strings [55][56][57][58], small-scale magnetic fields [59][60][61][62], the adiabatic cooling of matter [19,63], cosmological recombination [64][65][66][67][68][69], gravitino decay [70], and the dissipation of primordial density perturbations [20,21,[71][72][73][74][75][76][77][78][79][80][81] which is the main concern of this paper. Types of spectral distortions are characterized by the redshifts at which energy releases to CMB photons:…”
Section: Introductionmentioning
confidence: 99%
“…Signals from structures seeded by string loops have been studied in a recent paper by Schlaer et al [33] (see also [34] for earlier work) who found that loops could cause significant star formation to occur at high redshift. Therefore cosmic strings with enough mass will have an impact on the epoch of reionization [35,36]. String loops would also seed dense dark matter clumps.…”
Section: Introductionmentioning
confidence: 99%